Cultural ecosystem services of Lake San Pablo and their dynamics of change in the face of climate variability. - Vásquez Villacreses , Karla Daniela (SATHIRI, 2025)
Aquatic ecosystems are extremely vulnerable to the effects of climate change, with wetlands being among the ecosystems that have undergone the most significant changes in recent years as a result of these processes.  Lake San Pablo, the largest Andean and tectonic lake in Ecuador, is surrounded by several communities that use its sacred waters for spiritual, touristic, inspirational, educational, cultural, and aesthetic activities. The cultural ecosystem services (CES) provided by the lake are increasingly threatened by climate change; these services are key to preserving ancestral and traditional knowledge, which offers valuable techniques for all communities.  The objective of this research was to analyze the effects of local climatic variations on the cultural ecosystem services (CES) of Lake San Pablo: spiritual and religious, recreational and tourist, aesthetic, inspirational, educational, site identity, and cultural heritage. These services were characterized through surveys conducted with 123 residents living in the wetland's area of influence. The results showed that 74% of the population considers tourism the most important CES, followed by the spiritual and religious service with 40%. Climographs developed from 2013 onward indicate a decrease in temperatures and an increase in precipitation. Mapping carried out between 2000 and 2020 revealed a 0.598% loss in water surface area, a 0.12% increase in vegetative cover, and a 0.46% increase in non-vegetated areas. Finally, the seven CESs evaluated in Lake San Pablo in terms of climate change are vulnerable to the constant changes in precipitation and temperature showed over the years.
Keywords: San Pablo Lake; cultural ecosystem services; climatic variation; high Andean lakes